THE INFLUENCE OF THE IMPLEMENTATION OF MUHAMMADIYAH VALUES ON THE FINANCIAL MANAGEMENT PERFORMANCE OF A CAFETERIA OPERATING AT PKU MUHAMMADIYAH GOMBONG - Siti Barokah; Sri Ramlah (Journal of Global Business and Management Review, 2026)
This study aims to examine the influence of the implementation of Muhammadiyah values on the financial management performance of a cafeteria operating at PKU (Pembina Kesejahteraan Umat) Muhammadiyah Gombong. The cafeteria operates as a tenant within the PKU Muhammadiyah Gombong environment and is not formally classified as a Muhammadiyah Charitable Enterprise (Amal Usaha Muhammadiyah/AUM). This study employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to 60 respondents who were directly involved in financial management activities. Data were analyzed using validity and reliability tests, classical assumption tests—including normality and Glejser heteroscedasticity tests—and simple linear regression analysis with the assistance of SPSS statistical software. The results indicate that the implementation of Muhammadiyah values has a positive and significant effect on financial management performance, with a significance value of 0.000 (< 0.05) and a regression coefficient of 0.672. The coefficient of determination (R²) is 0.54, indicating that Muhammadiyah values explain 54% of the variation in financial management performance. These findings suggest that values such as amanah (trustworthiness), transparency, accountability, professionalism, and sincerity contribute substantially to improving financial management practices. This study concludes that the implementation of Muhammadiyah values can serve as an effective strategy for strengthening transparent, accountable, and sustainable financial management in business units operating within Muhammadiyah institutions, particularly cafeterias functioning as tenants in the PKU Muhammadiyah Gombong environment. AI Declaration: Artificial Intelligence (AI) tools were used solely for language editing and translation support during the preparation of this manuscript. The authors remain fully responsible for the originality, accuracy, interpretation, and integrity of the research content.